Picture Word Inductive Model (PWIM) Berbasis E-Learning dalam Pembelajaran Menulis Puisi Siswa Sekolah Dasar di Masa Pandemi Covid 19 - Pratiwi, Cerianing Putri (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
The purpose of this research is to know the use of picture word inductive based e-learning models to improve the poetry writing skills of Grade 4 student elementary school at the time pandemic Covid 19. This research is a class action study. Teachers and Grade 4 students elementary School are the source of data from this research. Data retrieval techniques using tests, observation techniques, and interviews. The procedures of each cycle on these studies are (1) Action planning, (2) Implementation of class actions, (3) Observations, and (4) reflections. The data analysis techniques used in this study are qualitative descriptive and comparative descriptive. The result of this research is the improvement of student poetry writing skills after the model of learning picture Word inductive based on e-learning models. At pre-action students were completed as much as 5.88% with an average class of 57.65. In the first cycle, after the actions of student writing test results have increased. Students who have a complete value of 82.35%, with an average class of 77.94. In this second cycle all students have been completed with an average grade of 85.59.